Multi-metal synchronous long-acting stabilized material as well as preparation method and application thereof

By iron modification of hydrotalcite, a multi-metal synchronous long-term stabilization material loaded with amorphous iron (hydrogen) oxides is solved, and the problem that traditional materials are difficult to deal with cationic and anionic heavy metals simultaneously in the treatment of polymetal pollution, achieving efficient and long-term stabilization effects, and improving soil fertility.

CN119709209APending Publication Date: 2025-03-28TSINGHUA UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411726003.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional stabilizing materials are difficult to treat cationic and anionic heavy metals simultaneously in the treatment of polymetal pollution, and aging accelerates in complex natural environments, making it difficult to maintain the stabilization effect for a long time.

Method used

By iron modification of natural clay mineral hydrotalcite, amorphous iron (hydrogen) oxide is loaded to form a multimetal synchronous long-acting stabilization material. The material adds ferric chloride solution at a uniform speed on the hydrotalcite matrix, and the iron element accounts for 20-30% of the mass of hydrotalcite. The pH value and temperature are controlled during the modification process to ensure the uniformity and stability of the material.

Benefits of technology

The synchronous long-term stabilization of multi-metals such as copper, zinc, cadmium, lead, arsenic, antimony has been achieved. The stabilization rate of heavy metals reaches more than 50%, maintains the stabilization effect for more than 2.5 years, and promotes the improvement of soil fertility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709209A_ABST
    Figure CN119709209A_ABST
Patent Text Reader

Abstract

The invention provides a multi-metal synchronous long-acting stabilized material and a preparation method thereof. The preparation method comprises the following steps: adding hydrotalcite into water, uniformly stirring, dropwise adding a ferric chloride solution for modification until the iron element accounts for 20-30% by mass of the hydrotalcite, keeping stirring after dropwise adding, filtering the obtained turbid liquid, and drying to obtain the multi-metal synchronous long-acting stabilized material. The prepared multi-metal synchronous long-acting stabilized material is applied to soil remediation. The multi-metal synchronous long-acting stabilizing material prepared in the invention can realize synchronous long-acting stabilization of composite heavy metal pollution of polycations including copper, zinc, cadmium and lead and polyanions including arsenic and antimony; and the soil fertility can be improved for a long time by immobilizing nitrogen, phosphorus and potassium nutrient elements in the soil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soil remediation and environmental functional materials, and in particular to a multi-metal synchronous long-term stabilization material and a preparation method and application thereof. Background Art

[0002] With the rapid advancement of urbanization and industrialization in my country, the problem of heavy metal pollution in soil is becoming increasingly serious. According to the "National Soil Pollution Status Survey Bulletin" jointly issued by the Ministry of Environmental Protection and the Ministry of Land and Resources in 2014, the national soil point exceeding the standard rate is 16.1%, of which inorganic pollutants (mainly heavy metals) exceeding the standard point accounted for 82.8% of the total exceeding the standard point. Stabilization technology is currently the most important technical means for the treatment of heavy metal pollution in soil in China. According to statistics, the adoption rate of stabilization technology in my country in 2018 was 48.5%. The main principle of stabilization technology is to add stabilization materials to contaminated soil to change the occurrence form of heavy metals in the soil, so that it is transformed from a mobile and easily bioavailable form to a more stable and less bioavailable form, thereby cutting off the exposure pathway between the pollution source and the receptor.

[0003] The existing patent CN202410144391.8 provides a calcium iron anion clay mineral material, a preparation method and an application; the preparation method of the calcium iron anion clay mineral material comprises the following steps: S1, providing a first mixed salt solution containing calcium ions and iron ions; S2, dropping the first mixed salt solution into water to obtain a second mixed salt solution; and in the process of dropping, maintaining the pH of the second mixed salt solution at 10 to 13; S3, aging the second mixed salt solution to obtain a reaction solution containing calcium iron anion clay mineral material; the aging temperature is 10 to 40°C. The present invention can not only remove cadmium and arsenic at a higher concentration (100 mg / L), but also realize efficient and stable remediation of cadmium and arsenic contaminated soil. ;

[0004] Existing patent 202410147933.7 provides an iron oxide / LDHs composite material, preparation method and application; the preparation method of the iron oxide / LDHs composite material comprises: ball-milling iron oxide and magnesium aluminum hydrotalcite together to obtain an iron oxide / LDHs composite material; wherein the mass percentage of the iron oxide and the magnesium aluminum hydrotalcite is 1-15%. The iron oxide / LDHs composite material provided by the present invention can improve the simultaneous treatment efficiency of cadmium and arsenic; it can not only remove cadmium and arsenic in water, but also stabilize the effective cadmium and arsenic in soil.

[0005] Traditional stabilization materials face serious problems in the treatment of multi-metal pollution. Due to the competitive adsorption between positively charged cationic heavy metals (such as copper, zinc, cadmium, and lead), and the existence of electrical antagonism between anionic heavy metals and anionic heavy metals (such as arsenic and antimony), it is very difficult to stabilize anionic and cationic polymetallic materials in the soil at the same time. In addition, under complex natural environmental conditions, factors such as rainfall leaching, acid corrosion, and ultraviolet irradiation will accelerate the aging of the material, making it difficult to maintain the stabilization effect for a long time. Therefore, the development of a multi-metal synchronous long-term stabilization material and its preparation method and application has important practical significance and broad market prospects. Summary of the invention

[0006] The purpose of the present invention is to provide a multi-metal synchronous long-term stabilization material and its preparation method and application, and to provide a modification method for the natural clay mineral hydrotalcite, so as to achieve the synchronous long-term stabilization of copper, zinc, cadmium, lead, arsenic and antimony pollution, with a heavy metal stabilization rate of more than 50%, maintaining the stabilization effect for more than 2.5 years, and promoting the improvement of soil fertility.

[0007] On the one hand, the present invention provides a method for preparing a multi-metal synchronous long-term stabilization material, the steps comprising: adding hydrotalcite to water and stirring evenly, adding ferric chloride solution dropwise for modification until the iron element accounts for 20-30% of the mass percentage of the hydrotalcite, and maintaining stirring after the addition is completed, filtering the obtained suspension and drying it.

[0008] Furthermore, the solid-liquid ratio of hydrotalcite to water is 1 g:(10-15) mL.

[0009] Furthermore, the hydrotalcite includes magnesium aluminum hydrotalcite or calcium aluminum hydrotalcite, and the size is 200-300 mesh.

[0010] Furthermore, in the magnesium aluminum hydrotalcite, the molar ratio of Mg / Al is 3:1; in the calcium aluminum hydrotalcite, the molar ratio of Ca / Al is 3:1.

[0011] Furthermore, the ferric chloride solution is added dropwise at a uniform speed, and the adding time is not less than 15 minutes.

[0012] Furthermore, the dropping speed of the ferric chloride solution is 4-6 mL / min.

[0013] Furthermore, the concentration of the ferric chloride solution is 90-105 g / L, preferably 96-97 g / L.

[0014] Furthermore, the modification temperature is 70-85°C, and the modification time is 1-2h.

[0015] Furthermore, the pH value during the modification process is 7-10.

[0016] Furthermore, the stirring speed is 1000-1500 rpm.

[0017] Furthermore, the drying temperature is 75-85°C and the drying time is 22-26h.

[0018] On the other hand, the present invention also provides a multi-metal synchronous long-term stabilization material prepared by the above method.

[0019] On the other hand, the multi-metal synchronous long-term stabilization material and the preparation method thereof in the present invention are applied to soil remediation.

[0020] Furthermore, the amount of the multi-metal synchronous long-term stabilization material used during soil remediation is 1-5% relative to the weight of the dry soil.

[0021] Furthermore, the soil includes single contaminated soil or composite contaminated soil of copper, zinc, cadmium, lead, arsenic and antimony.

[0022] The beneficial effects of the present invention are:

[0023] The multi-metal synchronous long-term stabilization material prepared in the present invention can achieve the synchronous long-term stabilization of complex heavy metal pollution including multiple cations including copper, zinc, cadmium, lead and multiple anions including arsenic and antimony; it can also improve soil fertility in the long term by fixing nitrogen, phosphorus and potassium nutrients in the soil.

[0024] The present invention provides a stabilizer and its preparation method and application for the soil contaminated by multiple cations (copper, zinc, cadmium, lead) and multiple anions (arsenic, antimony) composite heavy metals, which can modify the natural clay mineral hydrotalcite with iron, thereby achieving synchronous long-term stabilization under the condition of anion-cation composite heavy metal pollution. By loading amorphous iron (hydroxide) oxide on the hydrotalcite matrix, synchronous long-term stabilization of copper, zinc, cadmium, lead, arsenic and antimony pollution is achieved, the heavy metal stabilization rate is more than 50%, the stabilization effect is maintained for more than 2.5 years, and the soil fertility can be promoted. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 It is an infrared spectrum of the magnesium aluminum / calcium aluminum hydrotalcite and the iron-modified magnesium aluminum / calcium aluminum hydrotalcite in the present invention;

[0027] Figure 2 It is a mineralogical analysis diagram of the magnesium aluminum / calcium aluminum hydrotalcite and the iron-modified magnesium aluminum / calcium aluminum hydrotalcite in the present invention;

[0028] Figure 3 It is a scanned image of the magnesium aluminum / calcium aluminum hydrotalcite and the iron-modified magnesium aluminum / calcium aluminum hydrotalcite in the present invention. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] This embodiment provides a multi-metal synchronous long-term stabilization material, and the preparation steps include:

[0032] Preparation of magnesium aluminum hydrotalcite: Add an appropriate amount of deionized water to a beaker and adjust the pH of the solution to 10 using a 2M NaOH solution; then use AlCl3·6H2O and MgCl2·6H2O to prepare a precursor containing metal cations. The total Al 3+ The concentration is 0.1333M, and the molar ratio of Mg / Al is 3:1; in a reaction vessel, the precursor solution is added dropwise into a vigorously stirred NaOH solution, and a 2M NaOH solution is used to maintain the pH of the reaction solution constant within the range of 10±0.1, wherein the metal precursor solution is not added too fast to minimize the generation of impurities; the synthesis process is carried out in a 65°C constant temperature water bath; after the metal salt solution is added dropwise, the suspension is cured at 65°C for 18h; the precipitate is filtered and washed with deionized water for more than 3 times to remove excess sodium ions and chloride ions, and the collected solid sample is dried in an oven at 80°C for 24h and then ground to 200 mesh;

[0033] Magnesium aluminum hydrotalcite was added into water with a solid-liquid ratio of 1g:15mL. The mixture was continuously stirred at a speed of 1250rpm to make it evenly distributed in the water. An aqueous ferric chloride solution with a concentration of 96.5g / L was uniformly dropped into the reaction system at a speed of 5mL / min for modification until the mass percentage of iron element in the hydrotalcite was 25%. During the modification, the temperature of the reaction system was maintained at 80 degrees. The ferric chloride solution was added for >15 minutes. After the addition was completed, the stirring speed was kept unchanged and continued to be stirred. The modification time was 1 hour. During the modification, the pH of the reaction system was adjusted to 7 with a NaOH solution. The mixed suspension was filtered and dried in an oven at 80°C for 24 hours, and then ground to 200 mesh to obtain the final material for soil remediation.

[0034] Example 2

[0035] On the basis of Example 1, the magnesium aluminum hydrotalcite was replaced by calcium aluminum hydrotalcite, and the other steps and conditions were consistent with those in Example 1.

[0036] The preparation method of calcium aluminum hydrotalcite includes: adding an appropriate amount of deionized water to a beaker, and adjusting the pH of the solution to 12 using a 2M NaOH solution; then using AlCl3·6H2O and CaCl2·2H2O to prepare a precursor containing metal cations, with a total Al 3+ The concentration is 0.1333M, and the molar ratio of Ca / Al is 3:1; in the reaction vessel, the precursor solution is added drop by drop into the vigorously stirred NaOH solution, and 2M NaOH solution is used to maintain the pH of the reaction solution constant within the range of 12±0.1; the synthesis process is carried out in a constant temperature water bath at 65°C; after the metal salt solution is added dropwise, the suspension is cured at 65°C for 18h; the precipitate is filtered and washed with deionized water for more than 3 times to remove excess sodium ions and chloride ions, and the collected solid samples are dried in an oven at 80°C for 24h and then ground to 200 mesh.

[0037] Comparative Example 1

[0038] On the basis of Example 1, the ferric chloride solution was added all at once instead of being added dropwise at a uniform rate, and the other steps and conditions were the same as those in Example 1.

[0039] Comparative Example 2

[0040] Based on Example 1, the reaction system was not stirred after the ferric chloride solution was added dropwise, and the other steps and conditions were the same as those in Example 1.

[0041] Comparative Example 3

[0042] On the basis of Example 1, ferric chloride solution was added dropwise until the mass percentage of iron element in the hydrotalcite was 10%. Other steps and conditions were consistent with those in Example 1.

[0043] Comparative Example 4

[0044] On the basis of Example 1, ferric chloride solution was added dropwise until the mass percentage of iron element in the hydrotalcite was 50%, and other steps and conditions were consistent with Example 1.

[0045] Comparative Example 5

[0046] On the basis of Example 1, the temperature of the reaction system was kept at room temperature during the modification, and the other steps and conditions were consistent with those in Example 1.

[0047] Comparative Example 6

[0048] Based on Example 1, the pH of the reaction system was not adjusted during the modification process, and the other steps and conditions were consistent with those in Example 1.

[0049] Comparative Example 7

[0050] The magnesium-aluminum hydrotalcite was not modified and was directly added to the soil as a stabilizing material.

[0051] Comparative Example 8

[0052] The calcium aluminum hydrotalcite was not modified and was directly added to the soil as a stabilizing material.

[0053] The performance of the multi-metal synchronous long-term stabilization materials prepared in Examples 1-2 and Comparative Examples 1-8 was evaluated as follows:

[0054] A farmland in Guangxi, my country, was affected by upstream mining activities and was contaminated with copper, zinc, cadmium, lead, arsenic and antimony. The soil copper concentration was 116±1 mg / kg, zinc concentration was 677±25 mg / kg, cadmium concentration was 24.6±0.3 mg / kg, lead concentration was 204±4 mg / kg, arsenic concentration was 308±21 mg / kg and antimony concentration was 62.1±2.5 mg / kg.

[0055] When conducting short-term stabilization effect evaluation, contaminated farmland soil (soil particle size <2 mm) was collected, the obtained material was added to the soil at a dosage of 3%, 30% water was added and incubated for 3 days, and then leached to test the leaching rate of heavy metals;

[0056] When evaluating the long-term stabilization effect and soil fertility improvement effect, the obtained material was added to the farmland soil at a mass ratio of 3% (relative to the mass ratio of dry soil), coriander seeds were sown and watered appropriately. Soil samples were collected for leaching at intervals of 0.5 years, plant samples were collected at intervals of 1 year to test the heavy metal content, and the changes in soil nutrient content after 2.5 years were tested to study the heavy metal leaching rate before and after stabilization, the heavy metal content in plants, and the soil nutrient content.

[0057] (1) Evaluation of short-term soil stabilization effect

[0058] The soil to which the material was added was dried, then ground to <0.15 mm, and leached using the horizontal oscillation method, and the stabilization effect was indicated by the decrease in the concentration of copper, zinc, cadmium, lead, arsenic, and antimony in the leachate. The short-term stabilization effect is shown in Table 1 below, among which the short-term stabilization effect in Example 1-2 is the best.

[0059] Table 1

[0060]

[0061] (2) Evaluation of long-term effectiveness of soil stabilization

[0062] After adding the material, field soil samples were collected every 170-190 days to test the DTPA leaching concentration of copper, zinc, cadmium, lead, arsenic, and antimony, and plant samples were collected every 360-370 days to test the content of copper, zinc, cadmium, lead, arsenic, and antimony in plant tissues, for a total of 2.5-3 years. The long-term stabilization effect is shown in Table 2 below, among which the short-term stabilization effect in Example 1-2 is the best.

[0063] Table 2

[0064]

[0065]

[0066] (3) Evaluation of soil fertility improvement capacity

[0067] 2.5 to 3 years after adding materials in the field, soil samples were collected to test the contents of total organic carbon, total nitrogen, total phosphorus, total potassium, ammonium nitrogen (NH4-N), nitrate nitrogen (NO3-N), available phosphorus, and available potassium. The effect of the materials on improving soil fertility was evaluated based on the changes in the content of soil nutrient indicators before and after the addition of materials.

[0068] The heavy metal content in plants is shown in Table 3:

[0069] Table 3

[0070]

[0071] The soil nutrient index content is shown in Table 4 below:

[0072] Table 4

[0073]

[0074]

[0075] Based on the contents of the above table, the material prepared in the embodiment of the present invention has the effect of long-term reduction of heavy metal content in plants, and can also significantly increase the nutrient content in soil.

[0076] In the process of iron modification of hydrotalcite, the uniform addition of ferric chloride solution can ensure the uniformity and stability of the reaction, and avoid the problems of excessive local concentration, too fast reaction and acid-base imbalance of the system caused by one-time addition. The uniform addition can also effectively control the gradual deposition or incorporation of iron elements, maintain the pH stability of the reaction system, and prevent the generation of coarse and non-uniform iron oxide particles, ensuring the integrity of the layered structure of hydrotalcite and the best modification effect. The one-time addition of ferric chloride solution in Comparative Example 1 leads to uneven material modification, structural damage, and reduced performance, which in turn affects its actual application effect in soil remediation.

[0077] During the modification process, the reaction system is stirred after the ferric chloride solution is added, mainly to ensure the sufficiency and uniformity of the reaction and to prevent the generation of undesirable byproducts. After the ferric chloride solution is added, there may be local concentration differences in the system. Continuous stirring can make the reactants evenly distributed, avoid excess or insufficient iron ions in local areas, and thus promote the full progress of the modification reaction; stirring can also accelerate the diffusion of iron ions on the surface or crystal structure of hydrotalcite, ensuring the uniform incorporation or deposition of iron elements in the hydrotalcite material; continuous stirring can prevent the particles generated during the reaction from agglomerating, thereby obtaining a modified material with good dispersion and uniform particle size, and improving the performance of the material.

[0078] When the iron element accounts for 25% of the mass percentage of hydrotalcite, it can provide sufficient active sites, which is beneficial to improve the performance of the material in soil remediation, such as higher adsorption capacity, redox reaction efficiency or catalytic activity, that is, while maintaining the structural stability of the material, it can also give it good functional properties.

[0079] The iron content in Comparative Example 3 is too low to significantly change the physicochemical properties of the material, thereby failing to fully exert the effect of modification.

[0080] In Comparative Example 4, the iron element accounts for 50% of the mass percentage of hydrotalcite, which leads to the destruction of the balance between the metal ions of the hydrotalcite, and the collapse or disorder of the hydrotalcite crystal structure. High concentrations of iron may precipitate too many independent iron oxides (such as Fe(OH)3 or Fe2O3) during the reaction, resulting in the modification effect being mainly determined by these independent phases rather than the synergistic effect of hydrotalcite. In addition, high iron doping may introduce more lattice defects or impurities, reducing the structural integrity and thermal stability of the material; and excessive iron oxides may also over-cover the surface of the hydrotalcite, hindering the contact between pollutants and active sites, and reducing the adsorption or catalytic performance.

[0081] The increase in temperature will speed up the movement of the reactant molecules and increase the rate of the chemical reaction. When the reaction temperature is 80°C, the modification reaction between ferric chloride and hydrotalcite can be significantly accelerated, and the reaction time can be reduced. At higher temperatures, the diffusion rate of iron ions is faster, and they can be more evenly doped into the interlayer or surface of hydrotalcite to ensure the uniformity of the modification effect; and higher temperatures are conducive to the recrystallization and directional growth of hydrotalcite and modified products, forming a more stable layered structure. In comparative example 5, the modification was carried out at room temperature, and insufficient temperature would result in a large number of crystal defects in the material, affecting the performance of the final material.

[0082] LDH is easily dissolved under acidic conditions, causing its layered structure to be destroyed or collapsed. Alkaline conditions help maintain the structural integrity of the hydrotalcite, thereby ensuring the stability of the material during the modification process. Under alkaline conditions, iron ions are more likely to hydrolyze to form stable iron (hydroxide) oxide precipitates. These precipitates help to evenly adhere to or be doped on the surface or between layers of the hydrotalcite, thereby achieving effective modification of iron. If the pH is too low, the iron ions may not be completely precipitated, resulting in incomplete modification of the iron element. In addition, alkaline conditions can promote the uniform deposition of iron elements on the surface of the hydrotalcite, and form a stable modified layer through hydroxyl bridging or covalent bonding, thereby enhancing the synergistic effect between the modified hydrotalcite and the iron component.

[0083] In Comparative Examples 7 and 8, magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite are directly used as stabilizing materials and added to the soil. Based on Example 1 as a comparison, it can be known that iron modification can introduce iron-based active sites (such as Fe3+ or Fe2+) on the surface and interlayer of hydrotalcite. These active sites can enhance the adsorption capacity of the material and catalyze redox reaction performance, thereby improving the material's stabilization performance for multiple metals in the soil. Specifically: The original hydrotalcite has limited adsorption capacity for heavy metal ions. Through iron modification, the specific adsorption of heavy metal ions can be enhanced, thereby enhancing the stabilization effect. And iron ions have strong redox activity and can participate in electron transfer reactions. For example, with Fe 3+ / Fe 2+ When iron modification is involved, the As in the soil tends to be converted from the more toxic and easily mobile trivalent arsenic to the less toxic and less mobile pentavalent arsenic, greatly reducing the ecological risks caused by pollution; and iron modification may also enhance the thermal and chemical stability of hydrotalcite, making it exhibit a more lasting stabilization effect under long-term natural aging conditions.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a multi-metal synchronous long-term stabilization material, characterized in that the steps include: Add hydrotalcite into water and stir evenly, add ferric chloride solution dropwise for modification until the iron element accounts for 20-30% of the mass percentage of the hydrotalcite, keep stirring after the addition is completed, filter the obtained suspension and dry it.

2. The method for preparing a multi-metal synchronous long-term stabilization material according to claim 1, characterized in that: The hydrotalcite includes magnesium aluminum hydrotalcite or calcium aluminum hydrotalcite, and the size is 200-300 mesh.

3. The method for preparing a multi-metal synchronous long-term stabilization material according to claim 1, characterized in that: The ferric chloride solution is added dropwise at a uniform speed, with a dropwise addition rate of 4-6 mL / min, and a dropwise addition time of not less than 15 min.

4. The method for preparing a multi-metal synchronous long-term stabilization material according to claim 1, characterized in that: The concentration of the ferric chloride solution is 90-9105 g / L.

5. The method for preparing a multi-metal synchronous long-term stabilization material according to claim 1, characterized in that: The modification temperature is 70-85°C, and the modification time is 1-2h.

6. The method for preparing a multi-metal synchronous long-term stabilization material according to claim 1, characterized in that: The pH value during the modification process is 7-10.

7. A multi-metal synchronous long-term stabilization material, characterized in that: The method is prepared by any one of claims 1 to 5.

8. The preparation method of the multi-metal synchronous long-term stabilization material according to any one of claims 1 to 5 or the use of the multi-metal synchronous long-term stabilization material according to claim 6 in soil remediation.

9. The use according to claim 7, characterized in that The amount of the multi-metal synchronous long-term stabilization material used during soil remediation is 1-5% relative to the weight of the dry soil.

10. The use according to claim 7, characterized in that The soil includes single contaminated soil or composite contaminated soil of copper, zinc, cadmium, lead, arsenic and antimony.

Citation Information

Patent Citations

  • Iron oxide / LDHs (layered double hydroxides) composite material as well as preparation method and application thereof

    CN117960146A

  • Calcium-iron anion clay mineral material, preparation method and application

    CN118185632A

  • Magnetically modified hydrotalcite as well as preparation method and application thereof

    CN104707563A

  • Modified hydrotalcite / hydroxyl iron oxide composite material and preparation methods thereof

    CN109248647A

  • Preparation method and application of iron modified hydrotalcite-like compound

    CN118847027A